EVALUASI KINERJA APARATUR SIPIL NEGARA PADA KANTOR URUSAN AGAMA KECAMATAN KAPUAS MURUNG KABUPATEN KAPUAS - H Halus; B Bakhtiar (STIA Bina Banua Banjarmasin, 2020)
Abstract. This research has the test of seeing, analyzing and analyzing the performance of the State Civil Apparatus, Obstacles, and the at the Office of Religious Affairs, Kapuas Murung District, Kapuas Regency.This type of descriptive qualitative research. The key informant is the Head of the Office of Religious Affairs, the informant are, 1 person as the Head of the Head, and 2 Operational Staffs. Data techniques such as documents, observation and interviews. The collected data were analyzed qualitatively. This research shows: (1) Evaluation of the performance is carried out by assessing several elements, namely employee work goals, work behavior, additional value and creativity, generally in the good category, (2) Obstacles in evaluating the performance of the State Civil Apparatus regarding human resources that are still lacking in competence and morals in the assessment process, quality of employees, and the lack of education funds so that there are obstacles for every education and training that must be followed to improve work professionalism, (3) Solutions in overcoming problems related to the evaluation of the performance of the State Civil Apparatus, the Office of Religious Affairs, Kapuas Murung District, Kapuaprestasi District which is in accordance with administrative and technical duties in the field, improve the competence, improve the quality, Increase education and training funds, and Program for the development of human resources, as well as increasing knowledge and skills of the State Civil Apparatus at the Office for Religious Affairs, Kapuas Murung District, Kapuas Regency Abstrak. Penelitian ini bertujuan untuk mengetahui, mengevaluasi dan menganalisis kinerja Aparatur Sipil Negara, Kendala, dan Solusinya pada Kantor Urusan Agama Kecamatan Kapuas Murung Kabupaten Kapuas. Jenis penelitian deskriptif kualitatif. Key informan adalah Kepala Kantor Urusan Agama Kecamatan Kapuas Murung Kabupaten dan informan adalah Kasie sebanyak 1 orang dan Staf Operasional 2 orang. Teknik pengumpulan data berupa dokumen, observasi dan wawancara. Data yang terjumpul dianalisis secara kualitatif. Hasil penelitian menunjukan : (1) Evaluasi kinerja Aparatur Sipil Negara dilakukan dengan menilai beberapa unsur yaitu sasaran kerja pegawai, perilaku kerja, nilai tambahan dan kreativitas, secara umum dalam kategori baik, hal ini berarti dapat diukur, realistis, selaras dengan sasaran organisasi, (2) Kendala yang menyangkut evaluasi kinerja Aparatur Sipil Negara menyangkut adanya SDM yang masih kurang dalam hal kompetensi dan moral pada proses penilaian, kurangnya kualitas pegawai, serta minimnya dana pendidikan sehingga terdapat hambatan untuk setiap diklat yang harus diikuti untuk meningkatkan profesionalisme kerja. (3) Solusi dalam mengatasi kendala : meningkatkan kompetensi, meningkatkan kualitas, menambah dana Diklat, dan program pengembangan SDM, serta peningkatan pengetahuan dan keterampilan Aparatur Sipil Negara Kantor Urusan Agama Kecamatan Kapuas Murung Kabupaten Kapuas.